'Woorde in die mond gelê'? Psalmomdigting en die proses van kanonvorming - E. Kloppers (Acta Theologica)
In a previous article (HTS 2000/1:192–204) I have examined the process of versifying the Psalter and have questioned the principle of a so-called ‘reproductive’ versification, the lack of a sound hermeneutical approach, the necessity of versifying all 150 psalms — especially in one form and style as metrical psalms that are meant to be sung, and the liturgical function of many of the texts that had been versified in this manner. In this article the origin and history of these views are investigated and are evaluated against the background of the formation of canons on various levels. Some canonised views and traditions that need critical rethinking are indicated at the end of the article.